Chatbot as a Speaking Partner: an Applied Linguistics Study on AI Interaction in Enhancing English Speaking Ability - Chairunnissa Chairunnissa; Nazli Fahada; Saidatul Hanim; Insan Utama Sinuraya (CV. Pusdikra Mitra Jaya, 2026)
This study investigates the role of ChatGPT Voice as an AI-mediated speaking partner in enhancing English speaking ability among EFL learners from an Applied Linguistics perspective. The research employed a descriptive qualitative approach involving undergraduate students who experienced difficulties in spontaneous oral communication, low speaking confidence, and limited access to speaking partners. Data were collected through classroom observation, transcript documentation, and semi-structured interviews during several chatbot-assisted speaking sessions. The findings revealed significant improvement in five major indicators: fluency improvement, confidence increase, vocabulary expansion, response length, and speaking anxiety reduction. Learners gradually produced more continuous speech, longer responses, richer vocabulary, and greater interactional participation during human–AI conversation. The study also found that ChatGPT created a low-pressure communicative environment that encouraged learners to speak more freely without fear of negative judgment. In addition, AI-generated follow-up questions and conversational prompts stimulated discourse continuity and lexical development. The findings support communicative interaction theory, technology-mediated language learning, and AI-assisted willingness to communicate frameworks, which emphasize that oral proficiency develops through sustained and meaningful interaction. This study contributes a new perspective by positioning chatbot not merely as instructional technology, but as an autonomous communicative scaffold that facilitates human–AI interaction in speaking development. Therefore, chatbot-assisted communication can serve as an effective alternative for English speaking rehearsal in contexts where learners have limited opportunities for authentic conversational practice with native speakers.